L’évolution des rapports hiérarchiques entre directeurs et adjoints dans le champ de l’enseignement primaire de la Seine sous la IIIe République : aux origines d’une autonomie professionnelle - Jérôme Krop (Recherches en Éducation)
In France, school directors are not the hierarchical superiors of their colleagues, all of whom have the status of school teacher. This article goes back to the historical origins of this situation under the Third Republic, a period of recon-figuration of the field of primary education and the power relations between school directors and assistant teachers. This study is based on data collected during an exhaustive study of a representative body of files of teachers be-longing to the first generation of public school teachers who entered primary education in the Seine between 1870 and 1886. The analysis of the conflictuality between teachers and school directors shows how the history of social relations in the field of primary education has produced the practical arrangements rejecting the reconstitution of a hierarchical subordination by the sedimentation of schemas of education perception of authority relations.